KADAR HORMON TESTOSTERON, LIBIDO, DAN KUALITAS SPERMA KAMBING BLIGON, KEJOBONG, DAN PERANAKAN ETAWAH - , Laili Rachmawati; , Prof. Ir. Ismaya, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aim of the study was to investigate the comparison and correlation among testosterone concentrations, libido, and sperm quality of Bligon, Kejobong, and Etawah cross-bred (PE) bucks at the similar of age, feed, and season. Samples used were 9 bucks (3 Bligon, 3 Kejobong, and 3 PE) in Â±18 months of age. Testosterones was measured by enzyme-linked immunosorbent assay (ELISA) method. Libido observation were quantified at the first time to sniff, mount, and finally ejaculation. Sperm was collected by using artificial vagina, and correlation between testosterones, libido, and sperm quality was measured. Results showed that Kejobongâs testosterone in the morning (12.00Â±6.56 ng/ml) was significantly different with PE (6.82Â±4.18 ng/ml) (Pâ¤0.05), whereas Bligonâs testosterone in the morning (9.23Â±4.73 ng/ml) was similar with Kejobong and PE. The best time of Kejobongâs libido was in the morning (6.77Â±5.96